ANALISIS USABILITY TESTING PADA APLIKASI MOBILE BANKING MENGGUNAKAN METODE HEURISTIC EVALUATION - Diah Putri Utami; Laela Kurniawati (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Abstract A user interface display that is inappropriate or less user-friendly will result in users feeling uncomfortable, plus any problems that arise or errors occurring when using the application can make users potentially abandon the application they are using. This research aims to carry out usability testing on the M-Syariah mobile banking application, usability testing on an application is needed to identify problems with the interface and user experience so that recommendations for application improvements to increase user satisfaction can be made. Usability testing on the M-Syariah mobile banking application was carried out using the Heuristic Evaluation (HE) method. This HE method is based on 10 principles or aspects of usability according to Jacob Nielsen with a severity rating measurement scale. Measuring system usability in the M-Syariah mobile banking application using the HE method produces an average severity rating value of 1, namely the severity level is at the "Cosmetic Problem" level, from these findings the researcher then provides an improvement design as a recommendation that is in accordance with principles of heuristic evaluation and suggestions from respondents.